THE INFLUENCE OF WORK ENVIRONMENT, CAREER DEVELOPMENT, AND ORGANIZATIONAL SUPPORT ON EMPLOYEE WORK MOTIVATION A STUDY ON PT. INDONESIAN TUNA VARIETY GEMPOL PASURUAN, EAST JAVA - Rayhazziddan, Muhammad (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to investigate the influence of work environment, career development, and organizational support on employee work motivation at PT. Assorted Indonesian Tuna, Gempol Pasuruan, East Java. The research method used was a quantitative research with accidental sampling techniques on 125 respondents from various divisions of the company. Data collection was carried out through questionnaire deployment and data analysis using the SPSS application version 25, including validity, reliability, multiple linear regression analysis, t-test, F-test, and determination coefficient (r²) analysis, with a Likert scale for questionnaire measurements.The results of the analysis show that the work environment has a positive and significant effect on the work motivation of employees of PT. Aneka Tuna Indonesia, supported by the findings of similar previous research. Career development has also been shown to have a positive and significant influence on work motivation, in line with related research. In addition, organizational support is also significant in influencing employee work motivation, as the results of statistical tests show.The conclusion of this study is that all variables of work environment, career development, and organizational support together have a positive and significant effect on employee work motivation at PT. Various Indonesian Tuna. The practical implication of this research is the importance of companies considering these factors in an effort to improve their employees' work motivation